2020
DOI: 10.5194/essd-2020-291
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A national topographic dataset for hydrological modeling over contiguous United States

Abstract: Abstract. Topography is a fundamental input to hydrologic models critical for generating realistic streamflow networks as well as infiltration and groundwater flow. Although there exist several national topographic datasets for the United States, they may not be compatible with gridded models that require hydrologically consistent Digital Elevation Models (DEMs). Here, we present a national topographic dataset developed support physically based hydrologic simulations at 1 km and 250 m spatial resolution over c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Data include NWM‐R2 inputs and outputs, in situ measurements, and remotely sensed data from MODIS for water years 2008–2018. NWM‐R2 inputs that we used in our analysis were hourly NLDAS2‐based precipitation, hourly NLDAS2‐based air temperature, and elevation—derived from the 30 m Digital Elevation Model (Zhang et al, 2021)—with 1 km spatial resolution. We used NWM‐R2 outputs of 3‐h SWE and SCAF with 1 km spatial resolution from the land surface module.…”
Section: Model Data and Experimental Designmentioning
confidence: 99%
“…Data include NWM‐R2 inputs and outputs, in situ measurements, and remotely sensed data from MODIS for water years 2008–2018. NWM‐R2 inputs that we used in our analysis were hourly NLDAS2‐based precipitation, hourly NLDAS2‐based air temperature, and elevation—derived from the 30 m Digital Elevation Model (Zhang et al, 2021)—with 1 km spatial resolution. We used NWM‐R2 outputs of 3‐h SWE and SCAF with 1 km spatial resolution from the land surface module.…”
Section: Model Data and Experimental Designmentioning
confidence: 99%
“…While it was shown that anthropogenic activities reflected in USGS streamflow and WTD still contributed to the comparison bias, the results are encouraging with most of the gauges and wells having low relative bias and high Spearman's Rho scores. As Maxwell and Condon 38 indicated that the ParFlow simulation platform is evolving with more refined surface 89 and subsurface and more anthropogenic activities coupled, the model formulation will be improved.…”
Section: Usage Notesmentioning
confidence: 99%